Resistensi Simbolik dan Aktivisme Digital: Analisis Fenomena Garuda Biru dalam Mengawal Demokrasi dan Konstitusi Indonesia - Ajeng Iva Dwi Febriana; Yadi Kusmayadi; Anton Ardiansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
The planned ratification of the 2024 Regional Head Election Bill, which annulled the Constitutional Court's decision, triggered massive public resistance manifested through the